2022
DOI: 10.3389/fimmu.2022.1043572
|View full text |Cite
|
Sign up to set email alerts
|

A metabolite attenuates neuroinflammation, synaptic loss and cognitive deficits induced by chronic infection of Toxoplasma gondii

Abstract: BackgroundNeurodegenerative diseases including AD is currently one of intractable problems globally due to the insufficiency of intervention strategies. Long-term infection of Toxoplasma gondii (T. gondii) can induce cognitive impairment in hosts, which is closely implicated in the pathogenesis of neurodegenerative diseases. Aconitate decarboxylase 1 (Acod1) and its produced metabolite itaconate (termed Acod1/itaconate axis), have recently attracted extensive interests due to its anti-inflammatory role in macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 89 publications
2
10
0
Order By: Relevance
“…However, in contrast, activation of STAT1/3 by ACOD1‐induced ROS also caused cytokine accumulation 56 . Inhibition of ACOD1 causes microglia forming a protective subtype and promotes neuronal regeneration after parasite or virus infection 57,24 . Although the pathogenesis of post‐SCI neuroinflammation is triggered by mechanical injury‐induced fragmentised cells and tissue, our findings also suggested that the absence of ACOD1 aggravated OS and the inflammatory response in either SCI mice or debris‐treated microglia.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, in contrast, activation of STAT1/3 by ACOD1‐induced ROS also caused cytokine accumulation 56 . Inhibition of ACOD1 causes microglia forming a protective subtype and promotes neuronal regeneration after parasite or virus infection 57,24 . Although the pathogenesis of post‐SCI neuroinflammation is triggered by mechanical injury‐induced fragmentised cells and tissue, our findings also suggested that the absence of ACOD1 aggravated OS and the inflammatory response in either SCI mice or debris‐treated microglia.…”
Section: Discussionmentioning
confidence: 70%
“…Through protein modification of Keap1 via alkylation of its cysteine residues, Ita promotes Nrf2 expression, which enhances transcription of downstream genes that exert anti‐inflammatory/oxidative functions 19,21 . Because of this property, Ita and its derivative 4‐octyl itaconate (4‐OI) have been suggested as a potential target for the therapy of various diseases including liver injury, neuronal infection and pulmonary fibrosis 22–24 . Our recent study confirmed that the expression of ACOD1 was markedly increased in inflammatory microglia after LPS stimulation 25 .…”
Section: Introductionmentioning
confidence: 57%
“…Our previous study also showed that the derivative of itaconate could ameliorate the hippocampus-associated cognitive deficits in T . gondii infected mice [ 41 ]. Overall, these results suggest that itaconate may be a promising therapeutic molecular to treat neurodegenerative diseases including T .…”
Section: Discussionmentioning
confidence: 99%
“…gondii cysts by the gavage (10 cysts for each mouse) as Tg group. The detailed process of infection was carried out as previously reported [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, exogenous ITA reduces the bacterial burden, and the physiologic concentration of ITA is sufficient to control C. burnetii replication ( 43 ). Furthermore, in chronic infection with Toxoplasma gondii , which impairs cognitive functions, treatment of infected mice with DMI improves behavioral performance and ameliorates microglial inflammation ( 44 ).…”
Section: Roles Of Ita In Infectionmentioning
confidence: 99%